2018
DOI: 10.1016/j.amepre.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Screening Patient Decision Aids: A Systematic Review and Meta-analysis

Abstract: Context: Although screening recommendations for prostate cancer using prostate-specific antigen testing often include shared decision making, the effect of patient decision aids on patients’ intention and uptake is unclear. This study aimed to review the effect of decision aids on men’s screening intention, screening utilization, and the congruence between intentions and uptake. Evidence acquisition: Data sources were searched until April 6, 2018, and included MEDLINE, Scopus, CENTRAL, CT.gov, Cochrane repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
5
22
0
Order By: Relevance
“…The results in the current study support educational program efficacy in gaining knowledge among Jordanian men in Amman at one month after the implementation of the educational program. This finding is consistent with the findings of many studies (Drake et al, 2010;Keane, 2015;Ivlev et al, 2018). which showed that the educational program significantly improved cancer-related knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results in the current study support educational program efficacy in gaining knowledge among Jordanian men in Amman at one month after the implementation of the educational program. This finding is consistent with the findings of many studies (Drake et al, 2010;Keane, 2015;Ivlev et al, 2018). which showed that the educational program significantly improved cancer-related knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of educational program efficacy on adherence intention to a healthy lifestyle, the results showed that the adherence intention to healthy lifestyle variable improved significantly after 1 month form the application of the educational program. This finding is congruent with the finding of the previous research studies (Odedina et al, 2014;Keane, 2015;Ivlev et al, 2018), which showed that educational program significantly improved the adherence intention to a healthy lifestyle. An important possible explanation for the improvement in the adherence intention to a healthy lifestyle in the present study is the significant improvement in the level of knowledge regarding prostate cancer after the application of the educational program.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the effect of the prostate cancer educational program on intention to screen, the results of the current study showed that the intention to screen variable improved significantly 1 month after the application of the educational program in the experimental group compared to the comparison group. This finding is congruent with the finding of the previous research studies (Odedina et al, 2014;Keane, 2015;Ivlev et al, 2018), The finding of this study suggests that PCS intention may be influenced by PC educational program. This explanation was supported by evidence in previous literature, which showed a statistically significant increase in intention to screen, after an educational intervention (Odedina et al, 2014;Capanna et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Lastly et al, (2000), compared an illustrated pamphlet to a traditional pamphlet and noticed that both increased the level of knowledge, but neither increased the real usage of PSA testing. Similarly, other investigators reported a high knowledge score about PC and PCS, among respondents, after receiving the educational intervention (Drake et al, 2010;Keane, 2015;Ivlev et al, 2018). The significant effect of the prostate cancer educational program on knowledge may be attributed to many factors.…”
Section: Discussionmentioning
confidence: 84%
“…30 Decision aids could potentially improve patient knowledge prior to screening and have been used to improve knowledge for other screening programmes. [31][32][33][34] They could be used to explain the diagnostic test, conditions that could be diagnosed, quantitative information relating to diagnostic accuracy and the risks and benefits of treatment. They could also be used to promote clarification of patients' preferences about the screening and potential consequences to improve patient knowledge.…”
Section: Practice and Policy Implicationsmentioning
confidence: 99%